A polyoxovanadate as an advanced electrode material for supercapacitors - Chen, Han-Yi (2014)
Polyoxovanadate Na6V10O28 is investigated for the first time as electrode material for supercapacitors (SCs). The electrochemical properties of Na6V10O28 electrodes are studied in Li+-containing organic electrolyte (1 m LiClO4 in propylene carbonate) by galvanostatic charge/discharge and cyclic voltammetry in a three-electrode configuration. Na6V10O28 electrodes exhibit high specific capacitances of up to 354 F g−1. An asymmetric SC with activated carbon as positive electrode and Na6V10O28 as negative electrode is fabricated and exhibits a high energy density of 73 Wh kg−1 with a power density of 312 W kg−1, which successfully demonstrates that Na6V10O28 is a promising electrode material for high-energy SC applications.